Navigating the Competitive Landscape: The Drivers and Consequences of Competitive Aggressiveness - Ferrier, Walter J. (Academy of Management Journal, 2001)
By defining strategy as a sequence of competitive actions carried out over time, I develop and test a dynamic process model of competitive interaction among firms. Results based on a sample of thousands of competitive actions carried out by rivals competing in 16 different industries over a seven-year period suggest that characteristics of firms' sequences of competitive actions account for differences in their relative performance. The findings also suggest that a firm's sequence of competitive actions is influenced by top management team heterogeneity, past performance, slack, and three important industry characteristics.